The Applied Fiqh Reasoning of Santri Kudus in the Development of Waqf Banks in Indonesia - Muhaimin; Abd. Jalil; Suhadi (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
In Indonesia, waqf banks have also been implemented under the Indonesian Waqf Board (BWI). In its implementation, this waqf bank is prioritized to be managed by the Pondok pesantren community with procedures that must be followed to be considered eligible to establish a waqf bank. The research examines how the perspective of Kudus santri on the concept and practice of waqf banks in Indonesia, and how the fiqh reasoning of Kudus santri in the development of waqf banks in Indonesia, as well as how the applied fiqh perspective on the development of waqf banks in Indonesia. This research uses two different sources of data collection collected by the researchers themselves, directly from the primary sources. In this case, the main source is related to the reasons and reasoning of santri fiqh in the Development of Waqf Banks in Indonesia. The results show that the perspective of the Kudus santri on the concept and practice of the Waqf Bank can accept on the basis that the issue is khilafiyyah. In addition, the reasoning for the development of the Waqf Bank of the Kudus santri leads to the integration of fiqh with institutional professionalism. Even the orientation of applied fiqh is more on the aspect of the Tathbiqi Waqf Bank. Applied, the Waqf Bank is valid because it is a tathbiq norm of cash waqf in reality.